2019
DOI: 10.1371/journal.pone.0218172
|View full text |Cite
|
Sign up to set email alerts
|

Re-examining the robustness of voice features in predicting depression: Compared with baseline of confounders

Abstract: A large proportion of Depression Disorder patients do not receive an effective diagnosis, which makes it necessary to find a more objective assessment to facilitate a more rapid and accurate diagnosis of depression. Speech data is easy to acquire clinically, its association with depression has been studied, although the actual predictive effect of voice features has not been examined. Thus, we do not have a general understanding of the extent to which voice features contribute to the identification of depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 56 publications
4
27
0
Order By: Relevance
“…Other less studied variables that may affect speech and may vary within a group, thus inserting noise, are height, weight, dialectal variant, energetic state at the time of speech elicitation, and intimacy . If these variables are statistically different between case and control groups, they can be better matched through techniques such as propensity score matching …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other less studied variables that may affect speech and may vary within a group, thus inserting noise, are height, weight, dialectal variant, energetic state at the time of speech elicitation, and intimacy . If these variables are statistically different between case and control groups, they can be better matched through techniques such as propensity score matching …”
Section: Discussionmentioning
confidence: 99%
“…29 If these variables are statistically different between case and control groups, they can be better matched through techniques such as propensity score matching. 106…”
Section: Report Comorbiditiesmentioning
confidence: 99%
“…Speech has been demonstrated to have diagnostic validity for Alzheimer's disease (AD) and mild cognitive impairment (MCI) in studies using machine-learning classification models to differentiate individuals with AD/MCI from healthy individuals based on speech samples [34][35][36][37][38][39][40][41]. Additionally, speech analysis has been shown to be able to detect individuals with depression [42][43][44][45], schizophrenia [46][47][48][49], autism spectrum disorder [50], and Parkinson's disease [51,52], and can differentiate the subtypes of primary progressive aphasia and frontotemporal dementia [53][54][55]. Classification models provide diagnostic validity for speech measures and could be used to develop tools for disease screening and diagnosis.…”
Section: Clinical Validationmentioning
confidence: 99%
“…Study with enough evidence suggested that speech signals (such as certain vowel, words and numbers) contain vocal biomarkers that could be great aid to pathologist for the disease diagnosis. Several machine learning algorithms showed superior accuracy in disease prediction including Parkinson, depression, cardio and other diseases [38][39][40]. In the light of finding, it can be hypothesized that whether viral infections contain disease specific vocal biomarkers for disease analysis.…”
Section: Cov Outbreaks and Future Perspectivesmentioning
confidence: 99%